Options for Data Reporting--EITI Standard, 2016 : The Good, the Better and the Best - World Bank Group (World Bank, Washington, DC, 2016)
The Extractive Industries Transparency Initiative (EITI) is an international standard to promote open and accountable management of natural resources. By encouraging governments, extractive companies, civil society and the public to engage in discourse around transparency of the extractive sector, it aims to facilitate the management of a country’s natural resource wealth to benefit all its citizens. The objective of this report is to present, in a structured form, data categories and their reporting formats, that can be used to standardize information generated under each EITI Requirement. The review conducted for this study included a sample of recent EITI Country Reports, as well as other initiatives and industry standards. ‘Good’ refers to reporting standards that meet the minimum data to be provided under each EITI Requirement. ‘Better’ typically refers to reporting standards that are enhancements of data covered under the good category. ‘Best’ refers to standard formats for reporting data that represent the highest international benchmarks and are considered to provide comprehensive information, beyond the minimum data requirements. The research team recommends a step by step approach to this, starting with a specific set of Requirements, across a number of countries. This would allow the EITI International Secretariat to develop a set of comparable statistics for various reporting entities, as well as start constructing guidelines for EITI implementers.